Forest as A Living Space: Rulership and Management in the Tenganan Pegringsingan Customary Forest, Karangasem Regency, Bali - Aloysius Gonzaga Dimas Bintarta Raharja; Muhammad Baiquni; Setiadi Setiadi (Faculty of Forestry Universitas Gadjah Mada, 2024)
Humans control their cultural environment, which is associated with biotic and abiotic environments, resulting in environmental sustainability. The indigenous community's existence in managing environmental resources must be examined more deeply from the perspective of human ecology. Therefore, this research aimed to examine and analyze the management of resources and environment, mainly the customary forest in the Tenganan Pegringsingan indigenous community. This research employed a participatory observation and spatial ethnography paradigm to understand the pattern of the Tenganan Pegringsingan customary forest management based on customary law (awig-awig), legal delegation (The Customary Forest Decree), and the access of stakeholders to the customary forest. The customary forest governance involved krama desa, the land inheritance rights owners of the Tenganan Pegringsingan indigenous community, and Penyakap, immigrants/krama sesambahan tillers in the customary forest. These three stakeholders had different spatial access to the customary forest as a place and a space.